Safety and efficacy of a feed additive consisting of vermiculite for all poultry and ornamental birds, all porcine species, equines, leporids, camelids, pets and other non‐food‐producing animals (Regal B.V.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of vermiculite as a technological feed additive for all poultry and ornamental birds, all porcine species, equines, leporids, camelids, pets and other non‐food‐producing animals. The FEEDAP Panel concluded that vermiculite is considered safe at 10,000 mg/kg complete feed for the use in feed for chickens for fattening and reared for laying/breeding and laying hens, and at 5000 mg/kg complete feed for piglets and pigs for fattening. No conclusion can be drawn on the safety of the product for ornamental birds, equines, leporids, camelids, pets and other non‐food‐producing animals. The Panel concluded that the use of vermiculite is safe for consumer and the environment. The additive is considered a skin and respiratory sensitiser. Inhalation and dermal exposure are considered a risk. Due to the lack of data, the Panel could not conclude on the potential of the additive to be an eye irritant. The FEEDAP Panel concluded that vermiculite is efficacious as anticaking agent in feed, when used at 10,000 mg/kg complete feed.